Phage cocktails and the future of phage therapy. (June 2013) - Chan, Benjamin K; Abedon, Stephen T; Loc-Carrillo, Catherine
Viruses of bacteria, known as bacteriophages or phages, were discovered nearly 100 years ago. Their potential as antibacterial agents was appreciated almost immediately, with the first 'phage therapy' trials predating Fleming's discovery of penicillin by approximately a decade. In this review, we consider phage therapy that can be used for treating bacterial infections in humans, domestic animals and even biocontrol in foods. Following an overview of the topic, we explore the common practice – both experimental and, in certain regions of the world, clinical – of mixing therapeutic phages into cocktails consisting of multiple virus types. We conclude with a discussion of the commercial and medical context of phage cocktails as therapeutic agents. In comparing off-the-shelf versus custom approaches, we consider the merits of a middle ground, which we deem 'modifiable'. Finally, we explore a regulatory framework for such an approach based on an influenza vaccine model.